CHATGPT IN LEARNING ENGLISH, IS IT POSSIBLE? - Pagansa Putri, Yulia; Fitri Handayani; Riyen Permata (ELP (Journal of English Language Pedagogy), 2025)
The integration of artificial intelligence in education has sparked discussions on its effectiveness, particularly in language learning. This study examines students' perceptions of ChatGPT in English language learning using a quantitative descriptive approach. The research involved 63 students from the English Education Study Program at Mahaputra Muhammad Yamin University, Solok, during the 2023/2024 academic year, selected through a total sampling technique. Data were collected using a structured questionnaire consisting of 20 statements, administered via Google Forms. Students rated their responses on a five-point Likert scale ranging from "strongly disagree" to "strongly agree." The results indicate that 58.6% of students expressed agreement with the use of ChatGPT in English learning, suggesting a generally positive perception. These findings highlight the potential of AI-driven tools in enhancing language learning, emphasizing the need for strategic implementation to maximize their benefits in English education.